MALARIA INCIDENCE IN EAST KUTAI, EAST KALIMANTAN, INDONESIA 2016: AN EPIDEMIOLOGY STUDY - Oktara Geovanny Saroza; Susilowati Andajani; Indah S. Tantular (Majalah Biomorfologi, 2022)
Highlights: 1. Most malaria infections found in East Kutai Regency were found within the male group and had high contact with forest areas.2. Malaria infections were found predominantly in the male group aged 25 to 34 years old.3. Most of the malaria infections found were caused by Plasmodium vivax. Abstract: Background: Malaria is endemic in Indonesia and knowing the factors that are involved in malaria infection will help the development of surveillance, prevention, and disease control. Objective: This study aimed to identify the profile of malaria infection and the vectors known in East Kutai Regency, Indonesia, in 2016. Material and Method: This research was a descriptive observational study with a cross-sectional design. The sample used was taken from the 2016 annual report of The Health Office, East Kutai Regency. We evaluated malaria indicators, disease distribution, incidence (age, sex, and occupation), plasmodium species found and known vectors. Result: In 2016, there were 55 confirmed cases of malaria infection in East Kutai. The Annual Parasite Index was 0.16 per 1,000. Malaria patients were dominated by males (85.5%), aged between 25-34 years old with a mean age of 29.56 years. Most of the patients lived in Rantau Pulung (41.8%). Most of the patients had work that had high contact with forest areas (70.9%). Most of the patients were infected with Plasmodium vivax (58.2%). Identified vectors were Anopheles balabacensis which was found in Kaliorang District. Conclusion: The East Kutai Regency was classified as Low Case Incidence Area with most cases found in males of 24 to 34 years old whose work had high contact with forest areas. The identified plasmodium species were Plasmodium vivax and Plasmodium falciparum while the identified vector was Anopheles balabacensis.